UPAYA MENIMBULKAN KEPERCAYAAN MASYARAKAT TERHADAP POLRI DALAM MEMBERIKAN KEAMANAN DI WILAYAH HUKUM POLSEK HILIRAN GUMANTI KABUPATEN SOLOK - Robert Cenedy; Rifka Zuwanda; Firdaus; Rangga Prayitno (Ekasakti Jurnal Penelitian dan Pengabdian, 2024)
Police in law enforcement are at the forefront before prosecutors and judges. The police are a frightening specter. Not because they have weapons ready to be thrust at any party if they break the law, but also because basic police morals and ethics have disappeared in this large institution. When a police figure appears with a scary face, tough and authoritative attributes, he considers the police to be a public enforcer, a beating tool, a rigid law enforcer, and a figure who has harsh behavior, so the police are symbolized as a scary figure.